Unravelling the diversity of Scalibregma Rathke, 1843 (Annelida: ‘Polychaeta’: Scalibregmatidae) from southeast Brazilian coast - Mendes, Samuel Lucas Da Silva Delgado; Rizzo, Alexandra E.; Paiva, Paulo Cesar De (Zootaxa, 2023)
Scalibregmatidae Malmgren, 1867 is a relatively small family of annelids, with only two taxa reported to Brazil. In this work, we expand the scientific knowledge of this group by presenting two new Scalibregma Rathke, 1843 species. The new species S. lanai sp. nov. and S. cinthyae sp. nov. were collected during an expedition to the Campos and Santos oceanographic basins. Scalibregma cinthyae sp. nov. is unique among its congeners by the presence of two rows of paired lobes on the mouth’s upper and lower lips, whereas S. lanai sp. nov. is unique among its congeners by the presence of two rows of paired lobes on the mouth’s lower lip, branchiae from chaetigers 3–5, and lyrate chaetae with equal tynes. We provide an identification key to all Scalibregma species.